If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(b+5)-3=11
We move all terms to the left:
-2(b+5)-3-(11)=0
We add all the numbers together, and all the variables
-2(b+5)-14=0
We multiply parentheses
-2b-10-14=0
We add all the numbers together, and all the variables
-2b-24=0
We move all terms containing b to the left, all other terms to the right
-2b=24
b=24/-2
b=-12
| 6(x/2-3)+10=-32 | | 8i-6=5i+6 | | 9y+3•(-3y+6)=18 | | 16z-6z-z=9 | | 2(m-160=44 | | 9x+8=11x8 | | 13=y/2+9 | | 3(q+9)=99 | | 36y=2 | | 8d-7=2d+17 | | (3x-2)=(2x+22) | | 2(m+6)=-4(m+2)+11m | | 4=x–6 | | -2.5x–9=16 | | 8v+11=-19+3v | | 6+q=4+5 | | 8-4(x-9)=-136 | | 1/2(y-6)=2y+10-y* | | 18,6=3x | | 6(t+6)=96 | | 3x-33=-3(x-1) | | 12+3/4x=24 | | 6(k-3)-8=-34=5k | | (2x-11)/4=7 | | 9v+4v-12v-v+4v=16 | | 10+y=57 | | 9y-5=4y | | 18,6=6z | | 14(d-4)=-68 | | 6(b=13)=84 | | 2+9y=92 | | 5(x+2)-7x=-5x+2+x+4 |